2016
DOI: 10.1074/jbc.m116.737684
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Ceramides, but Not Sphingomyelins, as Antagonists of Insulin Signaling and Mitochondrial Metabolism in C2C12 Myotubes

Abstract: The accumulation of sphingolipids in obesity leads to impairments in insulin sensitivity and mitochondrial metabolism, but the precise species driving these defects is unclear. We have modeled these obesity-induced effects in cultured C2C12 myotubes, using BSA-conjugated palmitate to increase synthesis of endogenous sphingolipids and to inhibit insulin signaling and oxidative phosphorylation. Palmitate (a) induced the accumulation of sphingomyelin (SM) precursors such as sphinganine, dihydroceramide, and ceram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 34 publications
7
44
0
1
Order By: Relevance
“…Significant correlations between C16:0 and C18:0 sphingomyelin and ceramide species suggest that sphingomyelin degradation is an important reservoir for sarcolemmal ceramide production. Strong inverse relationships between sarcolemmal sphingomyelin and insulin sensitivity suggest sphingomyelin itself may promote insulin resistance, although there is evidence to the contrary (41).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…Significant correlations between C16:0 and C18:0 sphingomyelin and ceramide species suggest that sphingomyelin degradation is an important reservoir for sarcolemmal ceramide production. Strong inverse relationships between sarcolemmal sphingomyelin and insulin sensitivity suggest sphingomyelin itself may promote insulin resistance, although there is evidence to the contrary (41).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…Indeed, this issue has been discussed further in a recently published Crosstalk "debate" sponsored by the Journal of Physiology where investigators took oppositional positions about the roles for ceramides as modulators of muscle function [81,82]. Despite this contention, the initial in vitro studies convincingly demonstrated that increasing ceramide content in skeletal muscle cells potently inhibits insulin signaling [42,83,84]. Conversely, pharmacological inhibition of ceramide synthesis or increased degradation of ceramides in myotubes, attenuates palmitate induced inhibition of insulin signaling [85].…”
Section: Ceramides In Musclementioning
confidence: 99%
“…Type 2 diabetes often associates with dyslipidemia (Tian et al 2015) which not only increases the risk of cardiovascular disorder and initiates atherosclerosis, but also aggravates insulin resistance through inhibiting insulin signaling in insulin-targeted tissues including skeletal muscles (Park et al 2016). In addition, chronic dyslipidemia causes lipid deposition and induces pancreatic lipotoxicity, thus impairing insulin secretion and promoting the progression of type 2 diabetes (Litwak et al 2015).…”
Section: Zdq Reduced Plasma Tc and Tg In Type 2 Diabetic Ratsmentioning
confidence: 99%